Characteristics of Hard Antler (Trophy) of Male Rusa Timor (Cervus timorensis Blainville, 1822) - Imbenai, Amram Weilan; Koibur, Johan Frederik; Yohanes, Chrysostomus Hieronymus; Palulungan, John Arnold; Pattiselanno, Freddy (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2026)
Antler shape played a more important role in group dominance than body size. Until recently there was no available information on the morphometric size of antlers from native Indonesian deer in Manokwari, West Papua, Indonesia. This study was aimed to determine whether the morphometric size of left and right hard antlers differs in Timor deer from the Bird’s Head Peninsula of Papua Island; to assess whether morphometric measurements of hard antlers can serve as indicators of the distribution area of Timor deer in the region; and to evaluate whether other morphometric variables can reliably estimate hard antler length. This study employed a descriptive method, utilizing census techniques and direct observation of the antler owners in Manokwari Regency. A purposive sampling method is used in this study. Most of the antler’s collections originally from Teluk Wondama and Tambrauw regencies (six each), Teluk Bintuni and South Manokwari regencies (three each), Fakfak and Raja Ampat regencies (one each). The results of analysis indicate that the observed variables, based on morphometry values between left and right side of antlers from different areas of origin in this study, were almost symmetric and not significantly different. Similarities among variables measured (antler of length, length of first branch, length of second branch, length of the tip of main antler, antler diameter, main antler tip range, range of the second antler tip, range of the first antler tip, angle of the first branch), cannot be used as an indicator of the distribution of this sub-species in the Bird's Head Peninsula of Papua.